Early tangential excision and skin grafting in major burns - Hartati; Patricia Marcellina Sadikin. S (Science Midwifery, 2023)
Wounds are a form of tissue damage to the skin caused by directly contact with a heat source, the result of medical action, or changes in physiological conditions. Wounds cause disturbances in the function and structure of the body's anatomy. The body has a physiological response to injury, which is in the form of a wound healing process. This type of research is a case study conducted on Mr. MI, male patient and 38 years old. Techniques for analyzing and handling cases were employed as a family medicine approach. The case diagnosis was a deep dermal/full thickness burn (degree 2-3) with a 28% TBSA e.c flame which was classified as a severe degree burn. The patient experienced primary and secondary trauma management. Fluid resuscitation was administered using the Parkland formula. Wound care was performed by tangential excision, followed by covering the STSG. The patient went home with an improved condition after 3 days of treatment. His prognosis is generally good, but with the risk of functional limitations in the burn area.